1984
DOI: 10.1073/pnas.81.9.2743
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of a cDNA clone encoding mouse glial fibrillary acidic protein: structural conservation of intermediate filaments.

Abstract: A clone encoding mouse glial fibrillary acidic protein (GFAP) was isolated from a cDNA library constructed so as to express the cloned sequences. The library was screened using a GFAP-specific polyclonal antiserum; a single bacterial colony expressing GFAP was identified. The complete sequence of the cDNA insert in this clone is presented, encompassing 2.5 kilobases and specifying >97% of the GFAP amino acid sequence. The clone includes a long (1.4-kilobase) (GFAP). This protein is of particular interest be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
190
0
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(197 citation statements)
references
References 22 publications
(20 reference statements)
6
190
0
1
Order By: Relevance
“…There was no evidence of binding to either '5 or % RNA. This is consistent with previous studies using probes prepared from this vector (Lewis et al, 1984). Dot blot analyses of GFAP mRNA levels after lesions of the entorhinal cortex Quantification of GFAP mRNA levels in whole hippocampus by dot blot hybridization revealed that there were substantial increases in the levels of GFAP mRNA in the hippocampus after lesions of the entorhinal cortex (Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…There was no evidence of binding to either '5 or % RNA. This is consistent with previous studies using probes prepared from this vector (Lewis et al, 1984). Dot blot analyses of GFAP mRNA levels after lesions of the entorhinal cortex Quantification of GFAP mRNA levels in whole hippocampus by dot blot hybridization revealed that there were substantial increases in the levels of GFAP mRNA in the hippocampus after lesions of the entorhinal cortex (Fig.…”
Section: Resultssupporting
confidence: 79%
“…The probes used in this study were derived from a cDNA for mouse GFAP that has been characterized previously (Lewis et al, 1984). The original cDNA clone was 2.5 kilobases (kb) in length, which specified over 97% of the GFAP amino acid sequence, and also included a 1.4 kb long portion of the 3' untranslated region.…”
Section: Methodsmentioning
confidence: 99%
“…Sense and antisense RNA probes were transcribed in vitro with T3 and T7 RNA polymerase from linearized pBlusescript vectors carrying cDNAs for v-src, GFAP (Lewis et al, 1984), synaptophysin (Leube et al, 1989), proteolipid protein (Milner et al, 1985), VEGF (Breier et al, 1992),ÂŻk-1 andÂŻt-1 (Breier et al, 1995) in the presence of digoxigenin-11-dUTP (Boehringer Mannheim). 50 ± 200 ng of labeled transcripts (0.7 ± 1.2 kb) were hybridized to tissue sections at 658C as described (Marino et al, 1995).…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…A 34-mer oligonucleotide complimentary to nucleotides 358 to 391 of the mouse HSP25 sequence (Frohli et al, 1993) was used for mouse HSP25 mRNA. A 45-mer oligonucleotide complementary to nucleotides 1,119 to 1,163 of the mouse GFAP gene (Lewis et al, 1984) was used for mouse glial fibrillary acidic protein (GFAP) mRNA. A 39-mer oligonucleotide complimentary to nucleotides 1,872 to 1,910 of c-jun gene (Ryder and Nathans 1988) was used for cjun mRNA.…”
Section: In Situ Hybridizationmentioning
confidence: 99%